2016
DOI: 10.5901/mjss.2016.v7n3p302
|View full text |Cite
|
Sign up to set email alerts
|

The Relation Between Participation Motives and Goal Orientation of Participants in Recreational Dance Activities

Abstract: The aim of the study was to investigate: a) the participation motives of adults who take part in recreational dance activities, b) whether their demographic characteristics differentiate their participation motives and goal orientation and c) the relation between motivation and goal orientation. The study sample was 908 adult men and women, who participated in learning Greek dances. For the data collection, the method used was the Greek version (Patsiaouras, Keramida & Papanikolaou, 2004) of Participation Moti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Possible differentiation in the motives for participation in Greek dancing activities, depending on the demographic characteristics of the participants, has also been a previous research subject. The results of relevant studies have shown partial differentiation in the participants' motives depending on their gender, age, years of participation in the activity, educational level, previous dance experience and place of residence Doulias et al, 2005;Filippou et al, 2009;Goulimaris & Filippou, 2016).…”
mentioning
confidence: 99%
“…Possible differentiation in the motives for participation in Greek dancing activities, depending on the demographic characteristics of the participants, has also been a previous research subject. The results of relevant studies have shown partial differentiation in the participants' motives depending on their gender, age, years of participation in the activity, educational level, previous dance experience and place of residence Doulias et al, 2005;Filippou et al, 2009;Goulimaris & Filippou, 2016).…”
mentioning
confidence: 99%